ETIKA BISNIS DALAM PERSPEKTIF ISLAM (Lembaga Penelitian dan Pengabdian Masyarakat IAI An-Nadwah Kuala Tungkal, 2018)
The Business ethics is very important in regulating business activities undertaken by a businessman, especially a Muslim businessman who must run his business in accordance with Islamic. This ethics in Islamic economics is known as Islamic Business Ethics. Ethics or morals in business is the fruit of faith, Islam and piety based on belief in the truth of Allah SWT. In this paper is discussed about how the Islamic view of ethics in conducting business as well as the principles to business activies Islam is revealed by Allah in aiming to improve good morals or ethics. With the existence of Islamic business ethics is expected to maintain and maintain the perpetrators and business activities in accordance with the guidance of Islamic , not harming others and gain profit in the world and in the hereafter (falah).